Escherichia coli bloodstream infection preceding the diagnosis of rectal carcinoma. Issue 11 (17th October 2018) - Thoma, Reto; Häuptle, Pirmin; Degen, Lukas; Bassetti, Stefano; Osthoff, Michael
Abstract: Background: Cancer is one of the major comorbidities in patients with sepsis, and conversely, bloodstream infections (BSI) may precede the diagnosis of colorectal malignancy, in particular when Streptococcus gallolyticus is isolated. We present the rare case of an Escherichia coli BSI preceding the diagnosis of rectal adenocarcinoma. Case presentation: A 56-year-old man with a history of ocular myasthenia gravis presented with fever and shaking chills, and was diagnosed with E. coli BSI of unknown origin. After a thorough history and examination, diagnostic workup revealed a rectal adenocarcinoma as portal of entry for E. coli BSI. The choice of definitive antibiotic treatment was complicated by the risk of myasthenia gravis exacerbation by several classes of antibiotics. Conclusions: In patients with E. coli BSI of unknown origin, clinicians need a high index of suspicion regarding underlying colorectal malignancies. This may permit earlier diagnosis in a potentially curable stage.